Offering zero-rated content in the shadow of net neutrality - Giuseppe Colangelo; Valerio Torti (Market and Competition Law Review)
In the recent Telenor case, the EU Court of Justice has for the first time interpreted the relationship between net neutrality regulation and zero-rating offers, considering the former incompatible with the offer of packages in which data traffic generated by certain applications does not count towards the consumption of the data volume purchased and whereby, once that data volume has been used up, end-users may continue to use those applications without restriction, while other applications are blocked or slowed. However, despite their incompatibility with the net neutrality principle of non-discrimination, zero-rating offers may provide benefits to consumers, fostering broadband consumption and promoting product differentiation without necessarily leading to the exclusion of content providers. Therefore, a revision of the net neutrality regulation is needed in order to assess this practice in accordance with an ex post case-by-case investigation